Genetic and Functional Diversities of Microbial Communities in Amazonian Soils Under Different Land Uses and Cultivation - Cenciani, Karina; Mazzetto, Andre Mancebo; Lammel, Daniel Renato; Fracetto, Felipe Jose; Fracetto, Giselle Gomes Monteiro; Frazao, Leidivan; Cerri, Carlos; Feigl, Brigitte (IntechOpen, 2011)
None